2014
DOI: 10.1152/ajpgi.00471.2012
|View full text |Cite
|
Sign up to set email alerts
|

Fluorofenidone attenuates hepatic fibrosis by suppressing the proliferation and activation of hepatic stellate cells

Abstract: Z, Tao L. Fluorofenidone attenuates hepatic fibrosis by suppressing the proliferation and activation of hepatic stellate cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 50 publications
1
35
0
Order By: Relevance
“…Accordingly, its up-regulation may account for the activated cell death of hepatocytes at 9 weeks and inhibitory proliferation of liver cells at 6 and 9 weeks. Proliferation and activation of HSCs could be suppressed via ERK/MAPK in hepatic fibrosis (Peng et al, 2014), and p38 MAPK was also associated with cell apoptosis in liver fibrosis , so it could be concluded that the above two pathways, which were both enriched in Figure 6, play a vital role in cell growth and apoptosis/death during liver cirrhosis occurrence.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, its up-regulation may account for the activated cell death of hepatocytes at 9 weeks and inhibitory proliferation of liver cells at 6 and 9 weeks. Proliferation and activation of HSCs could be suppressed via ERK/MAPK in hepatic fibrosis (Peng et al, 2014), and p38 MAPK was also associated with cell apoptosis in liver fibrosis , so it could be concluded that the above two pathways, which were both enriched in Figure 6, play a vital role in cell growth and apoptosis/death during liver cirrhosis occurrence.…”
Section: Discussionmentioning
confidence: 97%
“…16,17 It can reduce fibroblast growth and collagen synthesis of different organs. [18][19][20][21] Furthermore, AKF is able to attenuate bleomycin-induced experimental IPF by reducing inflammation, accelerating the production of caveolin 1, inhibiting the phosphorylated MAPK-signaling pathway, and limiting the fibrosis cytokine TGF-β. 22 However, the curative power of AKF in the lung has been limited by its unsatisfactory pharmacokinetic properties, which include a short half-life (2 hours), as well as rapid absorption and extensive distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The human HSC cell line LX-2 was used in this study because of its similarity to primary human stellate cells; LX-2 cells express α-SMA, vimentin, platelet derived growth factor receptor β (PDGF-Rβ), matrix metalloproteinase (MMP)-2, and tissue inhibitor of matrix metalloproteinase (TIMP)-2 [6]. PI3K (phosphoinositide 3-kinase) is composed of an 85-kDa regulatory subunit and a 110-kDa catalytic subunit, which is recruited to and activated by the activated PDGF receptor following HSC activation and growth factor stimulation [7,8,9]. It has been reported that the activation of the PI3K/Akt pathway can facilitate HSC proliferation and α1 collagen expression [7,10,11].…”
Section: Introductionmentioning
confidence: 99%